2013
DOI: 10.1542/peds.2012-1725
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent ADHD and Adult Physical and Mental Health, Work Performance, and Financial Stress

Abstract: WHAT'S KNOWN ON THIS SUBJECT: There are a few longitudinal studies that suggest that attention-deficit/hyperactivity disorder (ADHD) in adolescence is associated with later psychiatric disorders, substance use disorders, and impaired work performance.WHAT THIS STUDY ADDS: Adolescent ADHD is associated with a variety of internal and external stresses in adulthood. Consequently, it is essential to focus intervention efforts on adolescents with ADHD to prevent or alleviate adult difficulties in functioning.abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 28 publications
3
55
0
3
Order By: Relevance
“…ADHD in adolescence also has a strong association with adult depressive mood and anxiety disorder [62]. A longitudinal study of 14-16-year-old teens two decades later found that adolescent ADHD was significantly associated with diminished physical and psychological health as well as an increased likelihood of antisocial personality disorder.…”
Section: Adulthoodmentioning
confidence: 99%
“…ADHD in adolescence also has a strong association with adult depressive mood and anxiety disorder [62]. A longitudinal study of 14-16-year-old teens two decades later found that adolescent ADHD was significantly associated with diminished physical and psychological health as well as an increased likelihood of antisocial personality disorder.…”
Section: Adulthoodmentioning
confidence: 99%
“…In regard to criminality, during periods under treatment with medication, individuals with ADHD presented lower criminality rates (measured as any conviction for a crime) compared to non-medicated periods. 79 Brook et al 80 recently studied the relationship between ADHD in adolescence and several outcomes in adulthood, and found that adolescents with ADHD are more likely to have impaired physical and mental health, antisocial personality disorder, impaired work performance, and high financial stress in adulthood. Raman et al 81 documented that the treatment with stimulants decrease the risk for injuries in children (see slide attached).…”
Section: Functional Outcomesmentioning
confidence: 99%
“…loses things, is forgetful, has difficulties organizing tasks, and fails to finish task. Adults with ADD live with the symptoms and suffer effects of the illness which attribute to their own shortcomings (Brook et al 2013).…”
Section: Introductionmentioning
confidence: 99%